Oxygen Defects Mediated Magnetism of Ni Doped ZnO - W. J. Liu; X. D. Tang; Z. Tang; W. Bai; N. Y. Tang (Advances in Condensed Matter Physics)
Ni doped ZnO nanoparticles were synthesized by a solution route and annealed in O2, air, and Ar, respectively. X-ray diffraction and X-ray photoelectron spectroscopy measurements show that the samples possess typical wurtzite structure and have no other impurity phases. Magnetization loops for ZnO samples were measured and clearly show typical ferromagnetic saturation behavior. With the defect analysis based on photoluminescence spectroscopy, the effect of defects on the nature and origin of ferromagnetism was investigated. The results suggest that oxygen vacancies, especially single ionized oxygen vacancies, play a crucial role in mediating ferromagnetism in the Ni doped ZnO.